Direct constraint on the Higgs–charm coupling from a search for Higgs boson decays into charm quarks with the ATLAS detector - Abidi, S. H.; Addepalli, S. V.; Aggarwal, A.; Camelia, E. Alunno; Antel, C.; Balaji, S.; Balek, P.; Bayirli, A.; Beddall, A. J.; Bhopatkar, V. S.; Bi, R.; Bielski, R.; et al. (European Physical Journal C, 2022)
A search for the Higgs boson decaying into a pair of charm quarks is presented. The analysis uses proton–proton collisions to target the production of a Higgs boson in association with a leptonically decaying W or Z boson. The dataset delivered by the LHC at a centre-of-mass energy of and recorded by the ATLAS detector corresponds to an integrated luminosity of 139 fb - 1 . Flavour-tagging algorithms are used to identify jets originating from the hadronisation of charm quarks. The analysis method is validated with the simultaneous measurement of WW , WZ and ZZ production, with observed (expected) significances of 2.6 (2.2) standard deviations above the background-only prediction for the ( W / Z ) Z ( → c c ¯ ) process and 3.8 (4.6) standard deviations for the ( W / Z ) W ( → c q ) process. The ( W / Z ) H ( → c c ¯ ) search yields an observed (expected) upper limit of 26 (31) times the predicted Standard Model cross-section times branching fraction for a Higgs boson with a mass of , corresponding to an observed (expected) constraint on the charm Yukawa coupling modifier | κ c | < 8.5 ( 12.4 ) , at the 95% confidence level. A combination with the ATLAS ( W / Z ) H , H → b b ¯ analysis is performed, allowing the ratio κ c / κ b to be constrained to less than 4.5 at the 95% confidence level, smaller than the ratio of the b- and c-quark masses, and therefore determines the Higgs-charm coupling to be weaker than the Higgs-bottom coupling at the 95% confidence level.